PSIKOEDUKASI PENINGKATAN MOTIVASI BELAJAR SISWA SMA PENABUR JAKARTA DI MASA PANDEMI - Raja Oloan Tumanggor (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Covid-19 pandemic has affected many aspects of people's lives, both from the economic, socio-political and health aspects. In terms of health, this pandemic has not only caused problems in the field of physical health, but also mental health. One of the groups exposed to mental health problems is students at the elementary, middle and college levels. The distance learning system implemented among high school students causes boredom, especially when it is coupled with a lot of assignments from teachers. This makes students bored and stressed. This situation is also experienced by students at SMA BPK Penabur, West Jakarta. Since distance learning was implemented 1.5 years ago, many students have experienced a decrease in motivation in learning, for example various changes in behavior from being diligent to being lazy, because they feel bored staying all day at home. At the time of online learning there are students who do not want to talk and are lazy to carry out lesson assignments. For this reason, students who are still in the youth category need to have adequate learning motivation in order to be able to take part in learning well, so that they can complete their education with good achievements as well. Therefore, the solution that will be offered in this PKM for teenagers is to increase motivation to learn during the pandemic, so that they can not only escape the temptation to be lazy, but also remain eager to learn, especially during the current pandemic. The outputs that will be produced are national proceeding articles, and a popular article in electronic media.Pandemi Covid-19 telah mempengaruhi banyak aspek kehidupan masyarakat baik dari aspek ekonomi, sosial politik dan juga kesehatan. Dari sisi kesehatan pandemi ini tidak hanya.menimbulkan permasalahan bidang kesehatan fisik, tapi juga kesehatan mental. Salah satu kelompok yang terpapar masalah kesehatan mental adalah para pelajar baik tingkat sekolah dasar, menengah maupun perguruan tinggi. Sistem pembelajaran jarak jauh yang dilaksanakan di antara siswa sekolah menengah atas menimbulkan kejenuhan, apalagi ditambah dengan banyak tugas dari guru. Hal ini membuat siswa menjadi bosan hingga stres. Situasi ini juga dialami oleh para siswa di SMA BPK Penabur Jakarta Barat. Sejak diberlakukan pembelajaran jarak jauh sejak 1,5 tahun lalu, banyak siswa mengalami penurunan motivasi dalam belajar, misalnya aneka perubahan perilaku yang sebelumnya rajin menjadi malas, karena merasa bosan tinggal sepanjang hari di rumah. Pada saat pembelajaran daring ada siswa yang tidak mau diajak bicara dan malas melaksanakan tugas pelajaran. Untuk itu para siswa yang masih dalam kategori remaja ini perlu memiliki motivasi belajar yang memadai agar mampu mengikuti pembelajaran dengan baik, sehingga dapat menyelesaikan pendidikannya dengan prestasi yang baik juga. Oleh sebab itu solusi yang mau ditawarkan dalam PKM ini bagi para remaja adalah meningkatkan motivasi belajar pada masa pandemi, sehingga mereka tidak hanya bisa lepas dari godaan untuk malas, tetapi juga tetap bersemangat untuk belajar khususnya di masa pandemi saat ini. Adapun luaran yang dihasilkan adalah artikel prosiding nasional, dan sebuah artikel popular di media elektronik.